Comparing the effects of glazing and chitosan-based coating applied on frozen salmon on its organoleptic and physicochemical characteristics over six-months storage. (February 2017) - Soares, N.; Silva, P.; Barbosa, C.; Pinheiro, R.; Vicente, A.A.
Abstract: The perishable nature of fish, with an increase in fish consumption in recent years, led to the improvement of fish preservation techniques. Chitosan coatings adds to the traditional water glazing. The effect of a chitosan solution of 1.5% on the sensory properties of Atlantic salmon ( Salmo salar ) was studied over six months of storage. The sensory properties of the salmon were assessed through the use of a texturometer and a trained panel of judges. Microbiological parameters were studied in the form of Total Volatile Base Nitrogen (TVB-N) and Total Viable Count (TVC) tests. Microbiological analysis showed that chitosan had an anti-microbiological effect on the salmon samples, reducing the number of microorganisms present, while TVB-N values were maintained stable during experiment. Textural Profile Analysis (TPA) was performed and the results showed no significant differences between different coatings regarding texture. Sensory analysis by a trained panel showed that chitosan was a better choice in frozen samples, while in thawed and cooked samples no significant differences existed between chitosan-coated and glazed samples. Flavor diffusion from the chitosan coating was assessed, and analysis of the results showed no correlation between coating type and sample flavor, indicating that no flavor diffusion had occurred. Highlights: Sensory assessment of a chitosan coating as an alternative to water glazing. Microbiological protection is better in chitosan coated samples. Sensory profiles similar for all coatings with no statistical difference present. Flavor diffusion from chitosan coatings does not occur.